2023
DOI: 10.1097/hjh.0000000000003444
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension prevalence by degrees of urbanization and altitude in Peru: pooled analysis of 186 906 participants

Abstract: Objective:Few studies, using countrywide data, examined how hypertension prevalence varies at diverse degrees of urbanization and altitude. This study examined the association between urbanization and altitude, including the potential interaction between those variables, with hypertension prevalence in Peru.Methods:Cross-sectional analysis of the Peruvian Demographic and Health Survey (2014–2019). Hypertension (SBP ≥140 mmHg or DBP ≥90 mmHg or self-reported diagnosis) was the outcome. Exposures were altitude l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(48 reference statements)
0
0
1
Order By: Relevance
“…Meanwhile, in the TOR-NASOL II study [38], it was reported that the prevalence of hypertension was lower in communities located above 3,000 masl, compared to those located below. Likewise, Mendoza-Quispe et al [39] reported that hypertension was lower in regions with altitudes higher than 2,500 and 3,500 m, compared to regions with altitudes lower than 1,500 m. However, there is a discrepancy with our findings in other studies conducted in populations residing at high altitudes. In studies conducted in Nepal, it was reported that the prevalence of hypertension and the mean SBP increased with altitude [15,40].…”
Section: Plos Onecontrasting
confidence: 99%
“…Meanwhile, in the TOR-NASOL II study [38], it was reported that the prevalence of hypertension was lower in communities located above 3,000 masl, compared to those located below. Likewise, Mendoza-Quispe et al [39] reported that hypertension was lower in regions with altitudes higher than 2,500 and 3,500 m, compared to regions with altitudes lower than 1,500 m. However, there is a discrepancy with our findings in other studies conducted in populations residing at high altitudes. In studies conducted in Nepal, it was reported that the prevalence of hypertension and the mean SBP increased with altitude [15,40].…”
Section: Plos Onecontrasting
confidence: 99%